1962
DOI: 10.1111/j.1365-3180.1962.tb00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Note on the Bioassay of Chlorpropham in Soil

Abstract: Summary. A method for the bioassay of chlorpropham in soil from field plots is described which involves the preparation of mixtures of treated soil with untreated soil and the determination of the dilution required to produce 50% inhibition of primary root growth in buckwheat (Fagopyrum esculentum Moench). Using this method, it was found that the period required for 90% disappearance of chlorpropham from a sandy foam ranged from 3 to 14 weeks, according to the prevailing temperature and soil moisture conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1963
1963
1977
1977

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
(10 reference statements)
1
0
0
Order By: Relevance
“…Sorghum had the second largest seed but was seventh in rate of root elongation. This is an agreement with RogIer (11), who concluded, on the basis of work done by Murphey and Arney (6) and Plummer (10), that in general, species with large seeds tend to have more vigorous seedlings than species with small seeds. Other workers (3,4,5) have shown that, within species, seed size markedly affects seedling vigor or rate of root elongation.…”
Section: Methodssupporting
confidence: 90%
“…Sorghum had the second largest seed but was seventh in rate of root elongation. This is an agreement with RogIer (11), who concluded, on the basis of work done by Murphey and Arney (6) and Plummer (10), that in general, species with large seeds tend to have more vigorous seedlings than species with small seeds. Other workers (3,4,5) have shown that, within species, seed size markedly affects seedling vigor or rate of root elongation.…”
Section: Methodssupporting
confidence: 90%